Governing Talent Selection through the Brain: Constructing Cognitive Executive Function as a Way of Predicting Sporting Success. Issue 2 (2nd April 2020) - Kilger, Magnus; Blomberg, Helena
ABSTRACT: An increasingly central part of the scientific debate in sports has come to focus on how neuroscience can help to explain sports performance and development of expertise. In particular, the process of identifying young talents has been increasingly influenced by neuroscientific tests to identify future potential. It has been argued that instead of relying on coaches' subjective assessments the process of selection should be based on general metrics of the brain through standardized testing. One key neurological function highlighted in the search for talent is cognitive executive functions. In the contemporary debate, studies of brain activity have suggested that children should undergo neuroscientific testing to determine the appropriate cognitive executive functions (CEF) for elite sports. This paper builds on previous work on the implications of a neuroscientific ontology in sports and Bruno Latour's work on the construction of scientific facts. Departing from discourse analysis, this paper studies the production and popularization of CEF as scientific facts. The findings illustrate how representations of brain activity are visualized and legitimized and how the out-of-context tests are translated into facts about brain functions. The CEF test results are produced as inscriptions of undisputable facts, claiming that the results show prerequisites for sporting success. We argue that the mind-brain-behaviour relationship cannot be reduced to CEF tests and instead calls for a critical gaze on neuroscientific truth-claims and taken-for-granted facts in the area of sport.